Negative impact on calorie intake associated with the 2006-08 food price crisis in Latin America - Iannotti, Lora; Robles, Miguel (SAGE Publications, 2011)
From 2006 to 2008, there were sharp increases in the prices of major food commodities globally, including maize, rice, and wheat. Few studies have contributed empirical evidence of the nutritional impacts of this food price crisis.To assess changes in energy intake in response to food price shocks and in relation to calorie adequacy levels in seven Latin American countries.Data were drawn from nationally representative household budget surveys. The quadratic almost ideal demand system (QUAIDS) model characterized change patterns in consumption for six food groups and one nonfood group under two scenarios: actual change in food prices by country, and standardized 10% increase in prices across all countries. Energy intakes before and after the crisis were determined once calories were assigned to food items from the ProPAN and US Department of Agriculture food composition databases.Energy intakes were reduced by 8.0% (range, 0.95% to 15.1%) from precrisis levels across all countries. Ecuador and Panama were the worst affected, followed by Haiti and Nicaragua. There was a consistent, direct relationship between wealth quintile and change in energy intake. Rural areas were affected to the same extent as or a greater extent than urban areas. High positive increases in calorie consumption were found in the richest wealth quintile, exceeding 10% of previous levels in five countries.Policies and programs targeting the poorest households in both rural and urban areas may be needed to offset the energy deficits associated with food price increases. More research is needed on the effect of food prices and micronutrient nutrition.